Analysis Effect of Loading on the DGA Results of the UAT 2A Transformer PLTU Paiton 1&2 for Optimizing Self-Use - Muhammad Faisol; Muhammad Hasan Basri (Postgraduate, University of Mataram, 2023)
In this study, the analysis of the effect of loading on the DGA results of the Paiton UAT 2A transformer units 1 and 2 was carried out using the DGA (Dissolved Gas Analysis) test tool with the X-DGA kelman tool to determine the gas content contained in oil or oil. The UAT 2A transformer is a type of oil-cooled distribution transformer that uses the Nytro Libra oil type. The oil in the UAT 2A transformer is useful for insulating and cooling media so that the UAT 2A transformer does not get hot. In the oil content there is a gas content that causes transformer failure. Gas failure is called gas fault which results in thermal and electrical failure. The results of the DGA (Dissolved Gas Analysis) test analysis show that loading greatly influences the DGA test results because there are contents that are indicated to experience Low Energy Electrical Discharge, Hight Energy Electrical Discharge and Thermal Fault, namely H2, CH4, C2H4, C2H6, C2H2, CO, CO2, and H2O continue to increase due to Thermal Fault